The Effect of Elderly Exercise on Blood Pressure Among Older Adults with Hypertension: A Quasi-Experimental Study - Nasir Muna; Hikmawati (Jurnal Ilmu Kesehatan Nusantara, 2024)
Background: Hypertension is one of the leading causes of cardiovascular morbidity and mortality among older adults worldwide. Regular physical activity, including elderly exercise, has been recommended as an effective non-pharmacological intervention to improve blood pressure control. However, evidence regarding the effectiveness of structured elderly exercise programs among hypertensive older adults in Buton Regency, Southeast Sulawesi, remains limited. Research Objective: This study aimed to determine the effect of an elderly exercise program on blood pressure among older adults with hypertension using a quasi-experimental design. Methods: A quasi-experimental one-group pretest–posttest study was conducted involving 32 older adults with hypertension selected through purposive sampling. Participants attended structured elderly exercise sessions three times per week for four weeks, with each session lasting 30–40 minutes. Blood pressure was measured before and after the intervention using a calibrated digital sphygmomanometer. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the paired-samples t-test with a significance level of p < 0.05. Results: The mean systolic blood pressure decreased from 154.8 ± 9.7 mmHg before the intervention to 144.2 ± 8.5 mmHg after the intervention, while the mean diastolic blood pressure decreased from 94.6 ± 6.4 mmHg to 87.8 ± 5.5 mmHg. The paired-samples t-test demonstrated statistically significant reductions in both systolic and diastolic blood pressure after the elderly exercise program (p < 0.001). Conclusion: The elderly exercise program effectively reduced blood pressure among older adults with hypertension. Integrating structured elderly exercise into routine community health services may enhance hypertension management and promote healthy aging.